Space Planning Concept Regarding the Area of Halal Food and Beverage Culinary - Anindya, Vania; Farisqi, M Reval Alfiadi (LifeSciFi, 2024)
Spatial planning in areas or restaurants that sell halal food is a strategic approach to create a safe, comfortable, and Islamically compliant environment. The main focus of this concept is to create an area that can support the provision of halal food and improve customer experience. Analysis of spatial planning in halal food restaurant areas aims to better understand and evaluate the effectiveness of spatial planning in supporting halal principles. This concept also includes various elements ranging from physical planning to social and cultural considerations. This analysis focuses on four main aspects, namely meeting halal food standards through area separation and the use of appropriate goods or materials, improving customer experience through ergonomic and more aesthetic design, operational efficiency that has supported a more optimal workflow and facilitated social interaction between visitors. The concept of areas or restaurants or places to eat that sell halal food in Indonesia not only focuses on providing food that meets halal requirements, but must also be able to create a comfortable, educational, and sustainable environment. With the support of the government, society, and business actors, this halal food area can become an attractive and innovative culinary center, so that it can contribute to economic growth and community welfare.